If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11 = v + 13 Reorder the terms: -11 = 13 + v Solving -11 = 13 + v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. -11 + -1v = 13 + v + -1v Combine like terms: v + -1v = 0 -11 + -1v = 13 + 0 -11 + -1v = 13 Add '11' to each side of the equation. -11 + 11 + -1v = 13 + 11 Combine like terms: -11 + 11 = 0 0 + -1v = 13 + 11 -1v = 13 + 11 Combine like terms: 13 + 11 = 24 -1v = 24 Divide each side by '-1'. v = -24 Simplifying v = -24
| 2.4(b-3)+3.8=-8.2 | | 7y=43 | | 1841.6728=2*232.2344+l | | 2.5p+5=20 | | y+9=24 | | 2b-8=30 | | -30=f-2 | | 3(5+4)-x=20 | | -4+-3x+x^2=0 | | 4y^2-10-3y=0 | | 26=3(10.5-.25y)-2y | | Y+5x+x=180 | | 2x^2+70x=1600 | | .5(2x+7)=.2x-2.1 | | 44000x^3+4000x^2+4000x-40000=0 | | 44x^3+4x^2+4x-40=0 | | 6x^2+80x+350=0 | | 7+5y-2y^2=0 | | y-2x^2=-8x+6 | | -0.75x-3=7.5 | | -5(v+2)+2v+5=5v+9 | | 12w+19w-6+5=-4w+5-6 | | 1672.992=2*162.7776+L | | 4x^2+4y^2+2x+12y-12=0 | | (p+13)-13=20 | | 3-3y=2(y+3) | | 7d=1 | | t-18+t=t+43 | | 9-6y=2(y+8) | | 2p+5p-47=5p | | 9+9+t=18+m | | 2p+5p+47=5p |